(untitled) (International Journal of Engineering & Extended Technologies Research (IJEETR), 2019)
High-growth digital platforms frequently face critical scaling limitations imposed by legacy architectural choices: monolithic web applications and rigidly coupled, single-server relational databases. These constraints—characterized by slow feature delivery, complex technology upgrades, and vertical scaling ceilings—are antithetical to the demands of rapid user acquisition and volatile traffic patterns. This paper proposes the Modular Web Application and Cloud Database Modernization Architecture (MWAC-DMA), a prescriptive framework for safely decomposing the monolith and migrating data to a scalable cloud-native ecosystem. MWAC-DMA mandates the use of Service-Oriented Architecture (SOA) principles for modularizing the application layer (Microservices/Modules) and leverages the Strangler Fig Pattern (SFP) for incremental database decomposition. Crucially, it utilizes a Dual-Write Synchronization Layer (DWSL) to enable seamless, low-risk migration from the legacy database to specialized cloud data stores (e.g., NoSQL, Managed Relational Services). The empirical analysis, based on a case study of a digital platform transition, demonstrates a 70% reduction in time-to-market for new features and a 100% elimination of downtime during the core data migration phase, establishing MWAC-DMA as a robust pathway for architectural renewal.